Mathematics-Based Development Module Problem-Based Learning Model to Improve Critical Thinking Ability - Novintya, Hertyas Tri; Suparman, S (Universitas Muhammadiyah Surakarta, 2018)
This study aims to produce a product in the form of a valid and practical problem based learning mathematics module based on critical thinking skills. This type of research is a 4D model development research which includes defining, planning, developing and disseminating stages. The results of the research were a valid and practical mathematical module on the social arithmetic material. The validity of the module reaches a very good category in terms of the expert judgment. The practicality of the module reaches a good category in terms of student assessment, and observation of learning implementation. The effectiveness of the module can be seen from the results of the t-test.